Analisis Pengaruh Variasi Putaran Spindel Dan Laju Pemakanan Dengan Pendingin CO2 Terhadap Kekasaran Permukaan Pada Proses Bubut Finishing Baja AISI 1045 - Rizal, Rio Abu; Asmadi, Asmadi; Budiman, Arie Yudha (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The lathe process is part of machining, namely The machining process was carried out on the outer surface of a cylindrical or flat workpiece using a lathe machine, followed by testing with three variations of spindle speed and feed rate to determine their effect on the surface roughness of the workpiece. Subsequently, tests were conducted using three different spindle speed and feed rate settings to evaluate their impact on the surface roughness of the resulting workpiece. In addition, from previous studies, the test results using variations of N (spindle rotation) with Rpm 255, Rpm 585, and Rpm 900, and Variation f (feed) 0.0803 mm / rev, 0.1229 mm / rev, 0.1700 mm / rev, whether the Ra value obtained decreased with increasing spindle rotation, and increasing feed rate will make the surface roughness of the workpiece rougher, the controlled variables in this study were AISI 1045 steel specimen material, spindle rotation speed, CO2 coolant. from the data obtained, the results of the Ra value that decreases are inversely proportional to the spindle rotation, in other words, the greater the spindle rotation, the smaller or smoother the Ra value produced. However, on the contrary, the faster the feed rate, the more directly proportional to the increasing roughness values ​​of Ra, in other words, the greater the feed rate, the greater or rougher the value and results of Ra.